Studi Aktivitas Antioksidan Senyawa 1-(p-klorobenzoiloksimetil)-5-fluorourasil dengan Metode Molecular Docking dan Metode DPPH (Antioxidant Activity of 1-(p-chlorobenzoyloxymethyl)-5-Fluorouracyl Using Molecular Docking and DPPH Method) - Brahmansyah Diar Rosiarto; Ayik Rosita Puspaningtyas; Diana Holidah (Pustaka Kesehatan, 2014)
Cellular damage caused by reactive oxygen species (ROS) free radical and antioxidant activity has an important role as free radical scavenging in body. This study was carried out to evaluate in vitro antioxidant and ligand afinity toward human ROS receptor (PDB code: 3ZBF). In DPPH method, 1-(p-chlorobenzoyloxymethyl)-5-fluorouracil dissolved in etil acetat, while 5-fluorouracil and ascorbic acid as standard dissolved in methanol. The free radical scavenging activity was measured spectrometrically with maximum wavelength at 512 nm. DPPH method show that ascorbic acid have strong antioxidant activity (IC50 = 19.092 ppm), while 1-(p-chlorobenzoyloxymethyl)-5-fluorouracil (IC50 = -2,500,245 ppm) and 5-fluorouracil (IC50 = -4,998 ppm) have not antioxidant activity. Molecular docking (in silico) toward human ROS receptor was indicate 1-(p-chlorobenzoyloxymethyl)-5-fluorouracil (Ki = -6.2 ± 0.04 kkal/mol) has best activity than ascorbic acid (Ki = -4.8 ± 0.19 kkal/mol) and 5-fluorouracil (Ki = -4.6 ± kkal/mol).   Keywords: 1-(p-chlorobenzoyloksimethyl)-5-fluorouracil, 5-Fluorouracyl, antioxidants, DPPH, molecular docking